Pemberdayaan Masyarakat Melalui Sistem Pemasaran Warkop Kopi Kampus (KOKAM) di Universitas Muhammadiyah Parepare - Dian Wahyudi; Muhammad Zainal; Dayu Suhardi; M. Jabir M; Adnan Adnan (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
The purpose of this service is to find out how and how much influence the use of the management control system (SPM) and marketing strategies implemented at the Campus Coffee Shop has to improve quality so that it can survive in the competition of similar coffee shop businesses. Marketing development strategy for campus coffee shops (KOKAM). Several approaches that can help coffee shops around campus increase their attractiveness and business success include understanding the target market, strong branding, menu variations, special promotions for students, collaboration with student organizations, a comfortable and instagrammable atmosphere, promotions on Social Media. Conclusion Warkop campus coffee (KOKAM) is growing and attracting more customers, prioritizing the quality of the products sold, warkop is a comfortable place with affordable coffee prices with the aroma and taste of coffee being the main attraction, by creating a variety of different coffee flavors, take advantage of social media platforms to introducing warkop.